Recurrent analysis of solar flare signals - Yerezhimbetova, А.S.; Abdigappar, U.; Alimgazinova, N.Sh.; Dauylbay, N.U. (Recent Contributions to Physics, 2021)
In this paper, the signals of the sun's X-ray radiation during solar flares are studied using the method of recurrent diagrams. The time fluxes of X-ray radiation at the wavelengths λ = 0.1 ÷ 0.8 nm and λ = 0.05 ÷ 0.4 nm, obtained by the GOES-15 (Geostationary Operational Environmental Satellite) space satellite, were used as the objects of the study. It was found that in the period from 2015 to 2019, the strongest solar flares occurred in September 2017 in the group of spots №2673. The causes of the X9,3 class flare from 06.09.2017 that occurred in this group of spots are analyzed in detail. Time and recurrent diagrams are plotted for each solar flare event. Analysis of recurrent diagrams for X -, M -, and C-class solar flare events revealed that soft X-ray radiation provides more information about the processes occurring on the Sun than hard X-ray radiation. It is shown that the method of recurrent diagrams more clearly captures the features and detects changes (periodicity) in a non-stationary non-uniform time series that corresponds to time intervals of high-energy solar events. Key words: Sun, group of spots, flare, X-ray radiation, nonlinear analysis, recurrent diagram